The Ubx Polycomb response element bypasses an unpaired Fab-8 insulator via cis transvection in Drosophila. - Danfeng Lu; Zhuoran Li; Lingling Li; Liping Yang; Guijun Chen; Deying Yang; Yue Zhang; Vikrant Singh; Sheryl Smith; Yu Xiao; Erlin Wang; Yunshuang Ye; et al. (PLoS ONE)
Chromatin insulators or boundary elements protect genes from regulatory activities from neighboring genes or chromatin domains. In the Drosophila Abdominal-B (Abd-B) locus, the deletion of such elements, such as Frontabdominal-7 (Fab-7) or Fab-8 led to dominant gain of function phenotypes, presumably due to the loss of chromatin barriers. Homologous chromosomes are paired in Drosophila, creating a number of pairing dependent phenomena including transvection, and whether transvection may affect the function of Polycomb response elements (PREs) and thus contribute to the phenotypes are not known. Here, we studied the chromatin barrier activity of Fab-8 and how it is affected by the zygosity of the transgene, and found that Fab-8 is able to block the silencing effect of the Ubx PRE on the DsRed reporter gene in a CTCF binding sites dependent manner. However, the blocking also depends on the zygosity of the transgene in that the barrier activity is present when the transgene is homozygous, but absent when the transgene is heterozygous. To analyze this effect, we performed chromatin immunoprecipitation and quantitative PCR (ChIP-qPCR) experiments on homozygous transgenic embryos, and found that H3K27me3 and H3K9me3 marks are restricted by Fab-8, but they spread beyond Fab-8 into the DsRed gene when the two CTCF binding sites within Fab-8 were mutated. Consistent with this, the mutation reduced H3K4me3 and RNA Pol II binding to the DsRed gene, and consequently, DsRed expression. Importantly, in heterozygous embryos, Fab-8 is unable to prevent the spread of H3K27me3 and H3K9me3 marks from crossing Fab-8 into DsRed, suggesting an insulator bypass. These results suggest that in the Abd-B locus, deletion of the insulator in one copy of the chromosome could lead to the loss of insulator activity on the homologous chromosome, and in other loci where chromosomal deletion created hemizygous regions of the genome, the chromatin barrier could be compromised. This study highlights a role of homologous chromosome pairing in the regulation of gene expression in the Drosophila genome.